PENGARUH PEMBIAYAAN JUAL BELI, PEMBIAYAAN BAGI HASIL, DAN NON-PERFORMING FINANCING TERHADAP PROFITABILITAS BANK PEMBIAYAAN RAKYAT SYARIAH - Roesmelyana, Firza Nazera; Sumiati, Ati; Susanti, Santi (Yayasan Education and Social Center, 2024)
This research was conducted to determine the effect of buying and selling financing, profit sharing financing, and non-performing financing on profitability. The research method used is a quantitative method with descriptive statistical analysis research type. The sample was obtained using a purposive sampling technique of 98 Sharia Rural Banks. This research uses secondary data obtained from the published financial reports of each bank on the Financial Services Authority website. Testing data analysis using SPSS 25. The results of this research show that partially buying and selling financing and profit-sharing financing do not have a significant influence on profitability. Meanwhile, non-performing financing has a negative and significant influence on profitability. Simultaneously, buying and selling financing, profit sharing financing, and non-performing financing have a positive and significant influence on profitability with a coefficient of determination of 13.6%.